Heating and Efficiency Comparison of a Fischer-Tropsch (FT) Fuel, JP-8+100, and Blends in a Three-Cup Combustor Sector. (20th November 2012) - Thomas, Anna E.; Saxena, Nikita T.; Shouse, Dale T.; Neuroth, Craig; Lynch, Amy; Frayne, Charles W.; Stutrud, Jeffrey S.; Corporan, Edwin; Hankins, Terry; Hendricks, Robert C.
Abstract : In order to realize alternative fueling for military and commercial use, industry guidelines be met. These aviation fueling requirements are outlined in MIL-DTL-83133F(2008) or ASTM D 7566-Annex standards and are classified as "drop-in" fuel replacements. This paper provides combustor performance data for synthetic-paraffinic-kerosene- (SPK-) type (Fisher-Tropsch (FT)) fuel and blends with JP8+100, relative to JP-8+100 as baseline fueling. Data were taken at various nominal inlet conditions: 75psia (0.52 MPa) at 500°F (533 K), 125 psia (0.86 MPa) at 625°F (603 K), 175 psia (1.21 MPa) at 725°F (658 K), and 225 psia (1.55 MPa) at 790 F (694 K). Combustor performance analysis assessments were made for the change in flame temperatures, combustor efficiency, wall temperatures, and exhaust plane temperatures at 3%, 4%, and 5% combustor pressure drop (% P ) for fuel:air ratios ( F / A ) ranging from 0.010 to 0.025. Significant general trends show lower liner temperatures and higher flame and combustor outlet temperatures with increases in FT fueling relative to JP8+100 fueling. The latter affects both turbine efficiency and blade/vane life. In general, 100% SPK-FT fuel and blends with JP-8+100 produce less particulates and less smoke and have lower thermal impact on combustor hardware.